Customers Level of Satisfaction of Esta’s Belle Boutique at Novaliches Proper Quezon City: Basis for Crafting a Proposed Guidelines SY 2022-2023: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, global trends in beauty, cosmetic, and personal care products are developing ata faster rate. For this reason, numerous businesses engaged in e-commerce to sell theirproducts. Supposedly, a lot of beauty and personal care products are increasing based onconsumer demand. Fake cosmetic and personal care items are among the concerns andproblems that Esta's Bella Boutique has encountered. They were able to distinguish fakeproducts from real ones by their physical differences. Thus, the owner only avails of stocksfrom trusted suppliers. This study aims to determine customers' level of satisfaction withEsta’s Bella Boutique in terms of price, brand, and quality.The results of this study reveal the customers' level of satisfaction with Esta's BellaBoutique; the satisfaction was evaluated as "very highly satisfied" in terms of price, brand,and quality. The problems encountered by the two groups concerning the product and thesolutions made by the owner in terms of "the products contain too many harmful ingredientswhich damage the skin" and there is a crafted proposed guideline to enhance the level ofsatisfaction of the customer.This study recommended that the business should consistently maintain the products itoffers to sustain customer satisfaction. Also, continue to implement affordable products fromreputed brands with quality and legal safety to prevent issues about products that containtoo many harmful ingredients that damage the skin. The researchers proposed guidelinesthat will enhance the level of satisfaction of the customers.Keywords: Business Administration
Keywords: Business Administration